A new species of small tree frog, genus Dendropsophus (Anura: Hylidae) from the eastern Amazon lowlands of Ecuador - Ortega-Andrade, H. Mauricio; Ron, Santiago R. (Zootaxa, 2013)
We describe a new species of the hylid frog genus Dendropsophus from Amazonian Ecuador. The new species, Dendrop-sophus shiwiarum sp. nov., appears to be part of the D. microcephalus species group. Dendropsophus shiwiarum differs from its congeners by a combination of: (1) tympanic membrane non-differentiated and annulus evident only ventrally, (2) disc of Finger III and Toe IV with pointed tip, (3) dorsal surfaces of digital discs with a conical tubercle as result of projection of distal phalanx, and (4) small size (SVL < 19 mm). The new species is morphologically most similar to Den-dropsophus riveroi. Examination of the type material of the latter suggests that some Ecuadorian populations reported as D. riveroi were misidentified and in fact belong to D. shiwiarum sp. nov.